Evaluasi Penerapan Tri Hita Karana di Daya Tarik Wisata Alas Kedaton, Desa Kukuh Kabupaten Tabanan - Megantari, Ni Made Sri; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA, 2020)
Alas Kedaton tourism attraction has participated in the Tri Hita Karana Tourism Awards and Accreditation 15 times. Although it has received the Super Platinum II Award from the Tri Hita Karana Bali Foundation, it does not cover the possibility that Alas Kedaton tourism attraction has negative issues. Therefore, the author evaluated the implementation of Tri Hita Karana in the attraction Alas Kedaton tourism attraction. In this research used the concept of evaluation, implementation and concept of Tri Hita Karana to dissect problems. The type of data used is qualitative and quantitative sourced from primary data and secondary data. Data collection techniques used with online interviews (telephone) and documentation. The technique of determining the informants technique used purposive sampling. Analysis of data used qualitative data analysis. Result of this research is the attraction Alas Kedaton tourism has done applications in accordance with The concept of Tri Hita Karana in the aspects of Parahyangan, Pawongan and Palemahan. But of course there are still some unintentional and unconscious shortcomings. Based on the results of the evaluation conducted by the researchers using the indicators Of Tri Hita Karana, there is one aspect that is quite much evaluated in The Aspect of Pawongan. While the aspect of Parahyangan And Palemahan has been applied very well. All indicators have been applied in according to their respective functions so that there are no overlaps with other indicators. Keywords: Evaluation, Tri Hita Karana, Implementation, Alas Kedaton tourism attraction